The black balloon [videorecording (DVD)] - Down, Elissa; Collette, Toni; Wakefield, Rhys, 1988-; Ford, Luke, 1981-; Thomson, Erik, 1967- (NeoClassic Films, 2010)
All Thomas wants is a normal adolescence, but his autistic brother Charlie thwarts his every opportunity. Will Thomas, with the help of his girlfriend Jackie, accept his brother?